Social Media Engagement and Student’s Intention in Indonesian Higher Education Using Unified Theory of Acceptance and Use of Technology - Matrissya Hermita; Budi Hermana; Suryadi Harmanto; Adang Suhendra; Munawir Pasaribu (Universitas Bumigora, 2023)
Understanding the motivations behind the use of social media in higher education is crucial for assessing its potential benefits and challenges. However, examining the contribution of social media on collaborative learning within the context of Indonesian universities holds significance due to the country’s growing digital landscape and increasing adoption of social media platforms. This research aimed to analyze proposed collaborative learning models involving social media use among Indonesian University students. The proposed models are constructed based on the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). The quantitative method used was analyzing primary data from 143 private university students in Indonesia. Data were collected using a 5-point Likert scale self-reported questionnaire of Internet Anxiety, Habit, and Performance Expectancy and Behavior Intention as well as Social Media Engagement to mediate collaborative learning. The result of this study was that Social Media Engagement and Behavior Intention significantly influence Performance Expectancy and Habit. There was also a significant influence of Internet Anxiety on behavioral intention. Thus, Collaborative Learning is significantly influenced by Social Media Engagement. These results provided insight into developing effective strategies for integrating social media into higher education.